2015
DOI: 10.1016/j.pharep.2014.08.017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carvacrol on systemic inflammation in guinea pigs model of COPD induced by cigarette smoke exposure

Abstract: These results showed a preventive effect of the carvacrol on all measured parameter in COPD guinea pigs which was comparable to the effect of dexamethasone at used concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 30 publications
2
48
0
1
Order By: Relevance
“…Serum MDA level and total WBC count in treated groups with two higher carvacrol concentrations; eosinophil, neutrophil, and lymphocyte percentage in those treated with high concentration; and IL-8 level and weight change in treated groups with all concentrations significantly improved compared to non-treated COPD group. The preventive effects of carvacrol were comparable to dexamethasone and demonstrated its anti-inflammatory effects (Mahtaj, Feizpour, Kianmehr, Soukhtanloo, & Boskabady, 2015). Therefore, plants containing carvacrol are effective remedies for preventing pulmonary obstructive diseases.…”
Section: Anti-inflammatory Activitymentioning
confidence: 84%
“…Serum MDA level and total WBC count in treated groups with two higher carvacrol concentrations; eosinophil, neutrophil, and lymphocyte percentage in those treated with high concentration; and IL-8 level and weight change in treated groups with all concentrations significantly improved compared to non-treated COPD group. The preventive effects of carvacrol were comparable to dexamethasone and demonstrated its anti-inflammatory effects (Mahtaj, Feizpour, Kianmehr, Soukhtanloo, & Boskabady, 2015). Therefore, plants containing carvacrol are effective remedies for preventing pulmonary obstructive diseases.…”
Section: Anti-inflammatory Activitymentioning
confidence: 84%
“…These studies indicated that guinea pigs develop COPD and emphysema-like lesions after a few months of exposure to active tobacco smoke [44] and physiological changes that mimic COPD in humans were showed in smoke-exposed guinea pigs [16, 44]. For example, in order to induce COPD in these animals, guinea pigs were exposed for 8-9 min to 5 cigarettes/day, 5 or 6 days per week for 3 consecutive months, with [50–53] or without filter [54–58], (Table 1). …”
Section: Cigarette-smoke (Cs)mentioning
confidence: 99%
“…Total WBC [51] and eosinophil counts in blood were increased in guinea pig models of CS-induced COPD [50, 53]. Total WBC, eosinophils and neutrophils in lung lavage of COPD guinea pigs were also increased [52].…”
Section: Inflammatory Cells and Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carvacrol decreased inflammation by various mechanisms such as inhibition of cyclooxygenase‐2 and subsequently decreased prostaglandin E2 production, reduced production of inflammatory mediators (eg TNF‐α, IL‐6, iNOS and IL‐10), and diminished levels of IL‐4, endothelin, IgE and eosinophil peroxidase, whereas it increased IFN‐γ in the serum of CAR‐treated sensitized guinea pigs . It also decreased white blood cell (WBC), eosinophil, serum levels of IL‐8 and malondialdehyde (MDA) in an animal model of chronic obstructive pulmonary disease (COPD) . Potent relaxant effect of CAR on tracheal smooth muscle, which was mediated through inhibition of histamine and muscarinic receptors, was also shown …”
Section: What Is Known and Objectivementioning
confidence: 99%